HEPATOSPLENOMEGALİ İLE BAŞVURAN BİR HBsAg TAŞIYICISINDA CASTLEMAN HASTALIĞI - BÜYÜKBEŞE, Mehmet Akif; ÖZDEMiR, Sebati; AKI, Hilal; SOYSAL, Teoman; PEKMEZCi, Salih; BAŞARANOGLU, Metin; ÖNGÖREN, Şeniz; SONSUZ, Abdullah; AKIN, Perihan (Cerrahpaşa Medical Journal, 2014)
Background and Observation.- 26 year old male patient admitted to outpatient clinics of Hepatology department because of the complaints of hiccups, malaise, and decreased exercise tolerance. HBsAg had been positiw for about elewn years. Physical examination rewaled hepatosplenomegaly and a suspected mass at the right inferior qantrant of the abdomen. In the computed tomography in addition to hepatosplenomegaly, a mass of 70x60x40 mm in dimension was noticed at the root of the mesentery and a decision for laparotomy was made. The histopathology of the mass extracted was documented as Castleman's disease of plasma cell variant. Two years later, he was doing well. Physical examination was unremarkable, and complete blood counts, biochemical and radiologic examinations were within normal limits. Literature is reviewed because of this case.